Analisis Kinerja Customer Service Officer dalam Meningkatkan Pelayanan Anggota di Kospin Jasa Capem Kedungwuni Kabupaten Pekalongan - Nida Sunniya; Mafturrahman, Mafturrahman (Politeknik Kampar, 2025)
Employee performance is the work result achieved by a person in carrying out their duties and responsibilities in accordance with the standards set by the organization. At Kospin Jasa Capem Kedungwuni, employee performance, especially in the position of Customer Service Officer (CSO), has an important role in creating a satisfying service experience for cooperative members. This study aims to analyze the performance of Customer Service Officer (CSO) employees in improving services to members at Kospin Jasa Capem Kedungwuni, Pekalongan Regency. The method used is qualitative descriptive with data collection techniques through observation, interviews and documentation. The results of the study indicate that the performance of Customer Service Officer (CSO) is quite good, indicated by a friendly attitude, professionalism, and understanding of member needs. However, there are several obstacles such as the limited number of Customer Service Officer (CSO) officers, long waiting times during peak hours, and challenges in dealing with members with diverse educational backgrounds. This study suggests increasing the number of Customer Service Officer (CSO) workers and optimizing the queuing system to support faster and more efficient services. These findings are expected to be strategic input for Kospin Jasa Capem Kedungwuni in improving the quality of member services.